Políticas públicas e agricultura familiar: Uma avaliação do PRONAF em dois assentamentos rurais da Mata Sul Paraibana. - Costa, Vibérica Gonçalves da (2013)
This Master´s dissertation on Environment and Development presents an evaluation of the National Program for Sustainable Family Agriculture PRONAF, specifically the PRONAF Credit Group A" destined for land reform settlers. The empirical cutting is two rural settlements located in the South Coast - the Forest Zone of the state of Paraiba. The central argument developed throughout this dissertation is that the Program is not effectively accomplishing its explicit objectives, such as, providing the increase in production capacity, generating employment and improving incomes of family farmers. It also aims to identify the profile of the communities studied taking into account the management and political organization of the settlers, economic, social and environmental aspects; get to know the default rates of the PRONAF settlements studied and the factors that affect the reimbursement of financed resources and raising activities that have the potential to be exploited in a sustainable manner in these communities. The evaluation methodology is based on qualitative conversations, field observations, questionnaires with open and closed questions that explain the perspectives of farmers regarding the above mentioned Program and the mapping and qualification of the socio-cultural qualitative indicators. The empirical research indicates the following aspects that contribute to the ineffective PRONAF A: high default rates (around 90.0 %) due to the fragility of infrastructure production, and poor access to productive and hydro technologies, loss-making and inadequate technical assistance. Even though they are located at southern coast, high period of drought undermine family agriculture production compounded by lack of access to productive and hydro technologies.